Cyclosporin A-loaded dissolving microneedles for dermatitis therapy: Development, characterisation and efficacy in a delayed-type hypersensitivity in vivo model - Miquel Martínez-Navarrete; Antonio José Guillot; Maria C. Lobita; María Carmen Recio; Rosa Giner; Juan Aparicio-Blanco; María Carmen Montesinos; Hélder A. Santos; Ana Melero (Drug Delivery and Translational Research, 2024)
Several drugs can be used for treating inflammatory skin pathologies like dermatitis and psoriasis. However, for the management of chronic and long-term cases, topical administration is preferred over oral delivery since it prevents certain issues due to systemic side effects from occurring. Cyclosporin A (CsA) has been used for this purpose; however, its high molecular weight (1202 Da) restricts the diffusion through the skin structure. Here, we developed a nano-in-micro device combining lipid vesicles (LVs) and dissolving microneedle array patches (DMAPs) for targeted skin delivery. CsA-LVs allowed the effective incorporation of CsA in the hydrophilic DMAP matrix despite the hydrophobicity of the drug. Polymeric matrix composed of poly (vinyl alcohol) (5% w/v), poly (vinyl pyrrolidine) (15% w/v) and CsA-LV dispersion (10% v/v) led to the formation of CsA-LVs@DMAPs with adequate mechanical properties to penetrate the stratum corneum barrier. The safety and biocompatibility were ensured in an in vitro viability test using HaCaT keratinocytes and L929 fibroblast cell lines. Ex vivo permeability studies in a Franz-diffusion cell setup showed effective drug retention in the skin structure. Finally, CsA-LVs@DMAPs were challenged in an in vivo murine model of delayed-type hypersensitivity to corroborate their potential to ameliorate skin inflammatory conditions. Different findings like photon emission reduction in bioluminescence study, normalisation of histological damage and decrease of inflammatory cytokines point out the effectivity of CsA-LVs@DMAPs to treat these conditions. Overall, our study demonstrates that CsA-LVs@DMAPs can downregulate the skin inflammatory environment which paves the way for their clinical translation and their use as an alternative to corticosteroid-based therapies. Graphical Abstract

Molecular topology: a strategy to identify novel compounds against ulcerative colitis - María Gálvez-Llompart; Maria C. Recio; Ramón García-Domenech; Jorge Gálvez (Molecular Diversity, 2017)